Double staining of bacilli and antigen Ag85B improves the accuracy of the pathological diagnosis of pulmonary tuberculosis. Issue 7 (27th November 2015) - Che, Nanying; Qu, Yang; Zhang, Chen; Zhang, Li; Zhang, Haiqing
Abstract : Background: A pathological examination plays an important role in the confirmation of a diagnosis of tuberculosis, especially for smear- and culture-negative cases. However, conventional Ziehl–Neelsen staining and histological tests lack sensitivity and specificity. Objective: To evaluate the diagnostic value of immunohistochemical staining to detect Mycobacterium tuberculosis protein Ag85B and a newly developed double staining (ZC staining) method that can simultaneously detect acid-fast bacilli and M. tuberculosis antigen in the same histological section. Methods: A total of 282 formalin-fixed paraffin-embedded lung tissues were identified following histological examination, including 212 cases of pulmonary tuberculosis and 70 other pulmonary diseases. Ziehl–Neelsen staining, Ag85B-immunohistochemistry and the newly developed ZC staining were performed on serial sections of all the specimens. Results: Expression patterns of Ag85B were consistent with the distribution patterns of acid-fast bacilli. The signal produced by Ag85B-immunohistochemistry was much stronger than that produced by Ziehl–Neelsen staining. The sensitivity of Ag85B-immunohistochemistry was significantly higher than that of Ziehl–Neelsen staining, 53.8% (95% CI 47.0% to 60.5%) vs 34.4% (95% CI 28.0% to 40.9%). The newly developed ZC staining, integrating advantages of both Ziehl–Neelsen staining and immunohistochemistry, further improved the rate of sensitivity up to 65.6% (95% CI 59.1% to 72.0%). Conclusions: This new method, detecting both acid-fast bacilli and M. tuberculosis antigen, is a simple and sensitive method for the pathological diagnosis of tuberculosis and can be easily incorporated into routine tests of pathological laboratories.